DOP45 Long-term cardiac safety of ozanimod in phase 3 clinical program of Ulcerative Colitis and relapsing multiple sclerosis. (21st January 2022) - Armuzzi, A; Cross, R K; Lichtenstein, G; Calkwood, J; Pai, A; Pondel, M; Ahmad, H A; Charles, L; Elegbe, A; Petersen, A; Sheffield, J K; Javed, A; et al.
Abstract: Background: Sphingosine-1-phosphate (S1P) receptor modulators may be associated with bradycardia and atrioventricular conduction delays. A previous analysis demonstrated first-dose ozanimod had minimal effects on cardiac function, including in patients (pts) with a known history of cardiovascular disease. This analysis evaluated long-term cardiac safety following continuous ozanimod treatment from the phase 3 ulcerative colitis (UC) True North trial and multiple sclerosis (MS) 12-mo SUNBEAM and 24-mo RADIANCE trials. Methods: Ozanimod 0.92 mg (equivalent to ozanimod HCl 1 mg)–treated pts from True North and pooled SUNBEAM/RADIANCE trials were included. In True North, pts in Cohort 1 received double-blind ozanimod or placebo and pts in Cohort 2 received open-label ozanimod in the induction period; in the maintenance period, pts with clinical response to ozanimod at 10 weeks were rerandomized to double-blind ozanimod or placebo. In True North, ECGs were monitored at screening, day 1, wk-10, and wk-52; heart rate (HR) was monitored at every visit. In the MS trials, ECGs were monitored at screening, baseline, day 15, and end of treatment (EOT); HR was monitored similarly at the beginning, then every 3 mo until EOT. Cardiac-related treatment-emergent AEs (TEAEs) were reported. Results: In the UC trial, continuous ozanimod treatment was not associated with any clinically significant changes in HR or ECG. The incidence of cardiac-related TEAEs with ozanimod during induction in Cohorts 1 and 2 was low (Table ). In maintenance, cardiac-related TEAEs were reported in 1.3% (3/230) of pts in the continuous ozanimod group (Table) ; incidence was numerically higher in ozanimod pts with (2 of 57 pts [3.5%]) versus without (1 of 173 pts [0.6%]) prior history of cardiovascular disease. Cardiac-related serious AEs (SAEs) were uncommon (angina pectoris, coronary artery stenosis, pericarditis in 1 patient each). In the pooled MS studies, no clinically significant HR or ECG changes were associated with chronic treatment up to mo 24. The incidence of cardiac-related TEAEs was low with ozanimod (Table ); incidence was similar among pts with (6 of 171 pts [3.5%]) versus without (24 of 711 pts [3.4%]) prior history of cardiovascular disease. Two of 882 patients experienced cardiac-related SAEs resulting in hospitalization with ozanimod in the MS studies (asymptomatic sinus bradycardia [HR 44 bpm] and symptomatic supraventricular tachycardia). Conclusion: Ozanimod had a manageable long-term cardiac safety profile with a low incidence of bradycardia and few serious long-term cardiac safety findings in the phase 3 UC and MS ozanimod trials.